The ideologies of a group of teachers-researchers in time of social isolation (Research, Society and Development, 2021)
This paper presents the analysis of reports of a group of professors-researchers in time of social isolation and the consequent rethinking of their practices. The socio-historical side of language is emphasized, conceiving the utterance as a product of interaction between socially organized subjects. To this do so, we present some ideologies and values that were present in discourses (in the form of a report) of professors-researchers who participate from the same research group. The methodology used is qualitative, of the case study type. The reports were obtained by filling out an online form and analyzed from the assumptions of the Bakhtin Circle, whereas discourse is not reduced to the linguistic system, because in it are present our interpretations and worldviews and that are configured with "ideologies". The analyses of the reports led us to four ideologies: (1) burden of the profession, (2) valorization of the teacher and science, (3) optimism about the moment experienced, opportunity and learning during isolation (lives) and (4) concern with the external. These aspects reflect a "time lived" by this group of professors-researchers, their anguish and perceptions of a historical and unique moment.